Soil pH change induced by smelting activities affects secondary carbonate production and long-term Cd activity in subsoils. (May 2023) - Wen, Junwei; Wu, Chen; Bi, Xiangyang; Zhang, Sili; Ouyang, Hao; Ye, Jiaxin; Ohnuki, Toshihiko; Yu, Qianqian
Abstract: Cadmium (Cd) is a typical element with contamination risk caused by anthropogenic sources. Cd is known to associate with Fe (hydr)oxides in pH-neutral to slightly acidic soils. However, field evidence on the effects of high pH on the long-term migration and redistribution of Cd in the soil is lacking. In this study, a comprehensive investigation of Cd, Pb, and Zn distribution in soils was performed at a Pb–Zn smelter site to unravel the pH control of long-term Cd activity in soils contaminated by non-ferrous metal smelting. Atmospheric deposition caused widespread contamination of the surface soil. In contrast, the discharge of heavy metals and alkaline waste liquid from two separate pollutant sources inside the smelter resulted in severe pollution migrating from the deeper layers up to a depth of 10 m. Elemental analysis showed that the Cd/Zn ratio in soil increased as the pH value increased, indicating that Cd was progressively decoupled from Zn and accumulated in the solid phase. Chemical extraction, SEM-EDS mapping, and micro-FTIR mapping analysis of soil particles revealed that most of the Cd were correlated with calcite, which formed as a secondary mineral at a higher pH. The production of secondary carbonate as a geochemical barrier enhanced the natural attenuation of Cd, which provides a reference for remediating Cd pollution. Overall, the results provide information for studying the transport and accumulation of heavy metals in deep soil layers. On the other hand, as carbonate is an unstable sink compared to other carriers, this mechanism should be considered in future studies on health and ecological risk assessment criteria for heavy metal pollutants in alkaline environments. Graphical abstract: Image 1 Highlights: Leaching of waste liquid brings severe pollution in deep layers up to 10 m in depth. Alkaline substances showed extreme vertical migration capacity. With increased pH value, Cd is progressively more enriched to Zn. Most of Cd correlated with secondary mineral carbonates at a higher pH. A comprehensive investigation of Cd distribution in soils near a smelter was performed.